MODIFIKASI KAMPIL PAKAN TERNAK BERBASIS ERGONOMI MEMPERBAIKI BEBAN KERJA DAN MENINGKATKAN RODUKTIVITAS KERJA PEKERJA PETERNAKAN AYAM BROILER - Saputra, I Kadek; Tirtayasa, Ketut; Sucipta, I Nyoman (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 3 No 1 (2017): Volume 3 No 1 Juni 2017, 2017)
One of important activity on broiler management is providing feed. Plastic bailer use to be use as supporting equipment. Base on working posture, working duration, repeating frequency and load haul it does not follow the ergonomic principles. Therefore, it can influence working load and productivity of farm worker. This research aim to prove that ergonomic intervention such feeding bag modification base on ergonomic can improve work load and increase work productivity of broiler farm worker.   This research is designed using pretest-posttest control group design. Twenty samples were selected with simple random sampling method and then allocated in to control group that use plastic bailer and intervention group that use feeding bag modification base on ergonomics to administer feed. The research was done in Suwegita Putra Chick Farm house located in desa Pajahan, Kec Pupuan, Kab Tabanan on Juni until Juli 2016. Evaluated variables were work load and work productivity of samples of broiler farm workers Research findings found that were decreasing heart rate about 13.7%, decreas cardiovascular load about 51%, increasing work productivity about 58.6%, and save the administration time about 51.9%. Therefore feeding bag modification base on ergonomic was significant (p<0.005) improving work load and work productivity. It could be concluded that feeding bag modification base on ergonomic improve work load and increase work productivity of broiler farm worker through work posture and work duration improvement, load haul adjustment. Finally, it can be expected that the research benefits can be implemented daily by broiler farm worker to achieve better general status.